Malaria Cytoskeletal Proteins Require Alveolin–Alveolin Interactions for Differential Localization - Ana Karla Cepeda Diaz; Peter S. Back; Sreelakshmi K. Sreenivasamurthy; Jeffrey D. Dvorin (Cellular Microbiology)
The alveolins are a family of intermediate filament-like proteins that form cytoskeletal structures in both free-living and parasitic members of the alveolate kingdom. Despite their important functions, the alveolins’ biochemical properties and organizing principles are still poorly understood. Here, we characterize four alveolins of Plasmodium falciparum, the deadliest malaria parasite, to understand how alveolin domains mediate protein–protein interactions and highly specific recruitment to substructures of the cytoskeleton. Unexpectedly, we uncover variable dependence on alveolin domains for each substructure rather than an overarching mechanism. While PfIMC1e requires 1f to be sequentially recruited to the basal complex, PfIMC1c and PfIMC1g do not require interactions with each other to localize properly to the inner membrane complex. Moreover, alveolin domains are not interchangeable—they contain unique signatures for specialized localization. Finally, we identify a region outside the alveolin domain of PfIMC1e that is important for basal complex recruitment. These results provide direct evidence that alveolin domains mediate both alveolin–alveolin interactions and compartment-specific localization.